The time-varying modal information of a cable-stayed bridge: Some consideration for SHM. (15th May 2021) - Li, Yixian; Zhu, Ledong; Qian, Cheng; Jian, Xudong; Sun, Limin
Highlights: Analyze the transient natural frequency and modal shape of a 1400 m-cable-stayed bridge. Adopt the direct analysis to calculate the time-varying transient modal information. Conclude the influence of wind effect on the cable-stayed bridge with different wind speeds and attack angles. Come up with the conditions in SHM where it is necessary to consider the influence of wind on the modal information. Abstract: With the increasing of bridge length, the nonlinearity and corresponding variation in modal information have become more obvious. For the in-operation bridges, the wind force is acting on the bridge nearly all the time, and whereas, the variation in modal information due to wind is not sufficiently studied. This paper has reported and discussed the variation in the bridge modes (natural frequency and modal shape) of a cable-stayed bridge under varied wind conditions. The Kaimal spectrum and the spectral representation method have been adopted to simulate the wind time-history. The wind-induced forces (including the aerostatic, buffeting, and self-excited forces) have been calculated adopting the aerodynamic coefficients and the flutter derivatives measured by a wind tunnel test. By applying the calculated wind forces to the nonlinear model of the bridge, the nonlinear responses of it are calculated. The modal information is calculated at each moment because the displacement field and stiffness matrix of the bridge are time-varying. In the numerical simulation section, the influences of the aerostatic, buffeting, and self-excited forces have been discussed to evaluate the influence of each component. Besides, the influence of wind speed and attack angle has also been discussed. The results have shown that the modal shape is more sensitive to wind forces than the natural frequency. In the daily wind environment, the influence of wind on the bridge modes is negligible. When the wind speed exceeds 10 m/s, the variation of modal shapes should be considered, and when the wind speed exceeds 16 m/s, the variations in both modal frequency and shape should be considered.